Spatial Dynamics Of Tsunami Prone Areas In Kalianda Sub-District, South Lampung Regency - Dita Wahyu Primastuti; Mangapul P. Tambunan; Triarko Nurlambang; Marlina Adisty (Eduvest - Journal of Universal Studies, 2024)
Kalianda Sub-District is one of the areas that is vulnerable to earthquakes and tsunamis because it is located on the west coast of Sumatra Island and the Sunda Strait has a potency from the eruption of Anak Krakatau Volcano. Increasing population growth also increases the risk of disaster impacts that are difficult to predict. This research aims to analyze the spatial dynamics of tsunami-prone areas in Kalianda District. This research uses multi-temporal land cover data, driving data on built-up land development factors, existing roads, slope, distance from the coastline, and distance from rivers. The method used is Cellular Automata Markov Chain which is used to model the development of built-up land, and the Berryman method for tsunami hazard analysis . Based on modeling results for 2031, the type of built land cover will experience a large increase. The tsunami danger level in Kalianda District is dominated by the low level covering an area of 4,741.80 ha, then the high level covering an area of 3,047.29 ha and the medium level covering an area of 1,243.66 ha. According to research results, the number of tsunami-prone areas increases every year. Therefore, we need to improve education and outreach to the public about tsunami dangers and effective evacuation procedures. The development and maintenance of evacuation support infrastructure, as well as the implementation of a reliable early warning system, are also very important to increasing community preparedness for tsunami disasters.